LEADERSHIP STYLE AND EMPLOYEE PERFORMANCE IN PARASTATALS: A CASE OF THE TRANSPORT SECTOR - M. Desderio, Chavunduka; Piason, Nyemba; Bhebhe, Thomas (IJRDO - Journal of Business Management, 2016)
Performance of most parastatals in Zimbabwe is dismal. Leadership styles used in the running of these parastatals could be a factor causing this poor performance. The purpose of the research was to investigate the relationship between leadership style and employee performance in the transport sector. Data was collected through administering a Multifactor Leadership Questionnaire (MLQ) for the leadership style and analysis of the employee performance appraisal records of the 178 respondents (34 managers and 144 raters/subordinates) in the selected parastatals. The data was analysed using the statistical package SPSS version 20. It was discovered that there were two main styles employed in this sector i.e. transformation and transactional leadership styles. Both styles were positively correlated to employee performance with transactional leadership style having a much stronger correlation. This implies that leadership styles are an important ingredient in the performance of parastatals.